LEGAL REVIEW OF THE SUPERVISION OF THE 2024 GENERAL ELECTION CAMPAIGN THROUGH SOCIAL MEDIA - Tobing, Rudyanti Dorotea; Kasenda, Dekie GG (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
One of the campaign methods in the 2024 election is campaigning through social media. In order for the implementation of the Election Campaign to run well and in accordance with the applicable laws and regulations, it is necessary to conduct supervision. Bawaslu is tasked with supervising the implementation of election campaigns, including monitoring campaigns on social media. The purpose of this research is first to describe the 2024 General Election Campaign through social media; second, to describe the Supervision of the 2024 General Election Campaign through social media. The method of normative legal research (legalresearch) using legal materials as the main source. The results of the study show that first, The presence of social media as a tool for disseminating information aimed at the public or voters in elections is considered an effective and important step, especially in shaping opinions and setting political agendas. In Central Kalimantan Province, there are four Social Media platforms registered and used by 2024 Election participants, including Instagram, Facebook, Tiktok, and Youtube. In Central Kalimantan Province there are 86 social media platforms for political parties and legislative candidate members. Second, Bawaslu of Central Kalimantan Province has formed a team to monitor the campaign via social media accounts during the 2024 Election stages. The large number of accounts on social media is an obstacle for Bawaslu to supervise campaigns on social media. Campaigns on social media are certainly in separable from the possibility of campaign violations on social media, including hoaxs or hate speech. The Election Law has not specifically regulated the limitations/prohibitions related to campaign violations on social media.